Prevalence and Predictors of Neonatal Sepsis among Neonates Admitted at the Newborn Unit of Kenyatta National Hospital, Nairobi, Kenya - Okube, Okubatsion Tekeste; Komen, Mercy (Open Journal of Obstetrics and Gynecology, 2020)
bidity and mortality especially in developing countries. Despite the availabili ty of different preventive interventions, in Kenya, the burden of neonatal sep sis remains critically high. Aim: To determine the prevalence and predictors of neonatal sepsis among newborns admitted at the newborn unit of Kenyatta National Hospital, Kenya. Methods: This is a hospital-based, cross-sectional study design carried out among 196 neonates and their mothers at the new born unit of Kenyatta National Hospital. A systematic random sampling technique was employed to select the study subjects. Data on the possible contributing factors of neonatal sepsis was collected using a semi-structured questionnaire. Statistical analyses were performed using the statistical pack age for the Social Sciences (SPSS: version 22). Data were descriptively ana lyzed into frequencies and proportions. The chi-square test of independence and binary logistic regression were employed to determine associations be tween the dependent (neonatal sepsis) and various independents variables. A multiple logistic regression model was carried out to determine the variables independently contributed to the occurrence of neonatal sepsis. Results: Our study revealed that the prevalence of neonatal sepsis was 28.6%. Neonates born of single mothers (AOR = 5.454, p = 0.012), mothers with history of UTI (AOR = 2.969, p = 0.013), PROM (AOR = 6.124, p = 0.001) and anaemia (AOR = 3.379, p = 0.010) were at higher risk to develop neonatal sepsis. Pre maturity (AOR = 6.402, p < 0.001), low Apgar score at 5th minutes (AOR = 8.212, p < 0.001) and history of invasive procedure (AOR = 2.464, p = 0.046) were the neonatal factors independently associated with neonatal sepsis. Conclusion and Recommendations: The prevalence of neonatal sepsis in Kenyatta National Hospital is high. This is another piece of evidence showing both maternal and neonatal-related factor had a significant effect on the risk of neonatal sepsis. Provision of community-based health education is highly recommended to increase awareness of women on the risk factors of neonatal sepsis and their preventive methods such as anaemia and UTI during preg nancy. Healthcare providers should exercise a high standard of care when handling premature and babies with low Apgar score to reduce the risks of neonatal sepsis.
Copyright © 2020 by author(s) and Scientific Research Publishing Inc. This work is licensed under the Creative Commons Attribution International License (CC BY 4.0). http://creativecommons.org/licenses/by/4.0/
Keywords: Preterm Birth; Neonatal Sepsis; Predictors of Neonatal Sepsis; Kenya